2023
DOI: 10.1186/s12866-023-02796-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence analysis of clinically isolated carbapenem resistant Escherichia coli from Iran

Abstract: Background The emergence of carbapenem-resistant Enterobacterales (CRE) continues to threaten public health due to limited therapeutic options. In the current study the incidence of carbapenem resistance among the 104 clinical isolates of Escherichia coli and the genomic features of carbapenem resistant isolates were investigated. Methods The susceptibility to imipenem, tigecycline and colistin was tested by broth dilution method. Susceptibility to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The PCR products were electrophoresed in a 1.5 % agarose with 1× TAE (Tris/Acetate/EDTA) buffer and DNA safe stain (Yekta Tajhiz Azma, Iran) and visualized under UV light using a Uvitec Gel Documentation system (Cambridge, UK). K. pneumoniae and Escherichia coli carrying the studied genes (identified during previous studies and confirmed for carrying the genes by sanger sequencing or whole genome sequencing ( 15 ) were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR products were electrophoresed in a 1.5 % agarose with 1× TAE (Tris/Acetate/EDTA) buffer and DNA safe stain (Yekta Tajhiz Azma, Iran) and visualized under UV light using a Uvitec Gel Documentation system (Cambridge, UK). K. pneumoniae and Escherichia coli carrying the studied genes (identified during previous studies and confirmed for carrying the genes by sanger sequencing or whole genome sequencing ( 15 ) were used as positive controls.…”
Section: Methodsmentioning
confidence: 99%
“…Although NDM and OXA-48 β-lactamases are more common to E. coli ST131, less common VIM, KPC and IMP β-lactamases were also reported in this species in some studies [68] . E. coli ST648, a high-risk pandemic clone, was reported in studies, each containing bla NDM–5 [78] , [79] . Other researchers looking at prevalence of STs among clinical E. coli reported ST131, ST405, ST648, ST410 and ST167, with ST167 most significantly associated with carbapenem resistance [80] .…”
Section: Carbapenemasesmentioning
confidence: 99%